Allergic march in children of Ukraine - Volosovets , О.P.; Bolbot , Yu.K.; Beketova, G.V.; Berezenko, V.S.; Umanets, T.R.; Rechkina , O.O.; Міtiuriaeva-Korniyko, I.O.; Volosovets, T.М.; Churylina , A.V. (Medicni Perspektivi, 2021)
Allergic diseases, which have a certain stage in their development from food allergy to bronchial asthma / allergic rhinitis, are much more common in children than in adults. The aim of this study was to analyze data on the prevalence and incidence of atopic dermatitis, bronchial asthma and allergic rhinitis as components of the allergic march, in children of Ukraine from 1994 to 2017 to determine the possible impact of adverse environmental factors on their development. During the same period, due to the influence of a number of factors, in particular environmental, there were significant changes in the structure of allergic diseases making up the stages of the allergic march due to an increase in the proportion of allergic rhinitis with the reduced one of asthma and atopic dermatitis. Within 24 years, the incidence of atopic dermatitis in children aged 0-6 years including, increased by 27.6%, in adolescents - by 40.5% and significantly decreased by 39.5% in children aged 7-14 years including. Most cases of allergic rhinitis and bronchial asthma were observed in schoolchildren (47.6 and 54.0%, respectively) with a slight decrease compared to 1994. In general, allergic diseases in recent years have become more common in children from 0 to 6 years and their detection has decreased in school-age children and adolescents. Over the past 24 years, in children of Ukraine a steady increase in the incidence and prevalence of allergic diseases that form an allergic march has been noted: the prevalence of bronchial asthma has increased by 69.3% and the incidence has increased by 22.9%; the prevalence of atopic dermatitis increased by 43.9% and the incidence increased by 8.3%; the prevalence of allergic rhinitis increased by 488.3% and the incidence of allergic rhinitis increased by 380.3%, with a predominance of detection of this pathology in children from regions with developed infrastructure and industry, where there are significant emissions of pollutants into the atmosphere, that have a direct moderate effect on the increase in the prevalence of bronchial asthma, the incidence and prevalence of allergic rhinitis in children.